Efektivitas Pembelajaran Imla' Di Kelas 2 TMI (Tarbiyatul Mu’allimin Al - Islamiyyah ) Pondok Pesantren Darussalam Kersamanah Garut - Sulaiman, Husnan; Az Zahra, Siti Laela (MASAGI : Jurnal Pendidikan Agama Islam, 2024)
The Effectiveness of Imla’ Learning in Grade 2 TMI (Tarbiyatul Mu’allimin Al-Islamiyyah) at Darussalam Islamic Boarding School, Kersamanah Garut. This study highlights the importance of imla’ (dictation) learning in enhancing Arabic writing skills, particularly within the context of Qur'anic instruction at Islamic boarding schools. The National Education System Law No. 20 of 2003 provides the foundation for religious education, including imla’. Professional educators in Islamic boarding schools are expected to integrate educational theory and practice, create a supportive learning environment for holistic development, and possess strong interpersonal skills. The objectives of this research are: 1) to identify the indicators of the effectiveness of imla’ learning in Grade 2 TMI (Tarbiyatul Mu’allimin Al-Islamiyyah), 2) to describe the implementation of imla’ learning, and 3) to evaluate the effectiveness of imla’ learning at Darussalam Islamic Boarding School, Kersamanah Garut. The research employs a qualitative method with a descriptive analytical approach. The study was conducted at Darussalam Islamic Boarding School, Kersamanah Garut, involving Grade 2 TMI students. Data sources include observations, interviews, and document studies. Data analysis techniques involve data reduction, data presentation, in-depth exploration in line with the research problems, and drawing conclusions to yield accurate findings. The results indicate that the indicators of effective imla’ learning include proficiency in writing Hijaiyah letters, understanding Arabic grammar, the ability to write sentences and verses from the Qur'an, and the capability to spell words correctly. The implementation of imla’ learning at Darussalam Islamic Boarding School encompasses initial, core, and concluding activities. This study concludes that imla’ learning at Darussalam Islamic Boarding School, Kersamanah Garut, is effective in enhancing the Arabic writing skills of students. Keywords: imla; learning effectiveness; Islamic boarding school